Theoretical Understanding of Structure–Property Relationships in Luminescence of Carbon Dots - Yu, Jingkun; Yong, Xue; Tang, Zhiyong; Yang, Bai; Lu, Siyu (The journal of physical chemistry letters, 2021)
Carbon dots (CDs) have excellent luminescence characteristics, such as good light stability, high quantum yield (QY), long phosphorescence lifetime, and a wide emission wavelength range, resulting in CDs’ great success in optical applications. Understanding the structure–property relationships in CDs is essential for their use in optoelectronic applications. However, because of the complex nature of CD structures and synthesis processes, understanding the luminescence mechanism and structure–property relationships of CDs is a big challenge. This Perspective reviews the theoretical efforts toward the understanding of structure–property relationships and discusses the challenges that need to be overcome in future development of CDs.